VIRTUAL EXPERIMENTAL STUDIES ON A NEW CONCEPT OF RELOCATABLE PLATFORM IN SHALLOW WATER - Rosli, Norsyahirah (IRC, 2019)
Throughout the history of oil drilling, marginal oil fields have been proven to be challenging in order to be developed. Moreover, the profits that can be achieved through this particular field has been decreasing throughout the years as the cost for its development has continually be on its high point.